The State of Coagulation, Anticoagulant and Fibrinolitic Parts of the Hemostasis System in Burn Shock - Yunusov Oybek Turaevich; Yunusova Guzal Fayzullayevna; Saydullayev Zayniddin Yakhshiboyevich (Genius Journals, 2023)
The problem of burns still remains one of the most urgent and complex in modern medicine. First of all, this is due to the significant spread of burns among the population, in connection with which it can be called without exaggeration a modern traumatic epidemic in densely populated cities and industrialized countries of the world, which is due to the continuing high level of this type of injury, the severity of its medical and social consequences. Burn shock and acute burn toxemia, especially severe, causes significant disturbances in the blood coagulation system. The state of hypercoagulability observed in the victims during the period of burn shock and toxemia requires appropriate correction for the prevention of thromboembolic complications.
Keywords: Burn shock; burn toxemia; prothrombin index; coagulation system